Short pulse and directional thalamic deep brain stimulation have differential effects in parkinsonian and essential tremor - Ute Hidding; Miriam Schaper; Alessandro Gulberti; Carsten Buhmann; Christian Gerloff; Christian K. E. Moll; Wolfgang Hamel; Chi-un Choe; Monika Pötter-Nerger (Scientific Reports, 2022)
Abstract The aim of this study was to assess the effects of novel stimulation algorithms of deep brain stimulation (short pulse and directional stimulation) in the ventrointermediate thalamus and posterior subthalamic area (VIM/PSA-DBS) on tremor in Parkinson’s disease (PD) and to compare the effects with those in essential tremor (ET). We recruited six PD patients (70.8 ± 10.4 years) and seven ET patients (64.4 ± 9.9 years) with implanted VIM/PSA-DBS in a stable treatment condition (> 3 months postoperatively). Tremor severity and ataxia were assessed in four different stimulation conditions in a randomized order: DBS switched off (STIM OFF), omnidirectional stimulation with 60 µs (oDBS60), omnidirectional stimulation with 30 µs (oDBS30), directional stimulation at the best segment with 60 µs (dDBS60). In both patient groups, all three DBS stimulation modes reduced the total tremor score compared to STIM OFF, whereas stimulation-induced ataxia was reduced by oDBS30 and partially by dDBS60 compared to oDBS60. Tremor reduction was more pronounced in PD than in ET due to a limited DBS effect on intention and action-specific drawing tremor in ET. In PD and ET tremor, short pulse or directional VIM/PSA-DBS is an effective and well tolerated therapeutic option. Trial registration: The study was registered in the DRKS (ID DRKS00025329, 18.05.2021, German Clinical Trials Register, DRKS—Deutsches Register Klinischer Studien).